Sacred Traditions and Tourist Gazes: Community Experiences of Heritage Tourism in Bali - Rizkikadduhani, Annisa (Advances in Tourism Studies, 2024)
Bali has become one of the most studied tourism destinations in Southeast Asia, often celebrated for its rich cultural heritage and ritual practices. Yet, as tourism expands, heritage is increasingly reshaped into performances tailored for visitors, raising questions about authenticity, commodification, and community agency. This study investigates how Balinese communities negotiate the tension between sacred tradition and tourist consumption in the context of heritage tourism. Using a qualitative approach, data were collected through in-depth interviews with cultural practitioners, temple caretakers, dancers, and local residents, alongside participant observation at temple festivals and staged performances. Thematic analysis reveals that while many residents view tourism as an opportunity to share culture and sustain livelihoods, they also express ambivalence toward the commercialization of rituals and performances. Narratives highlight strategies of negotiation, where authenticity is redefined as a balance between cultural integrity and economic survival. At the same time, concerns about cultural dilution and the erosion of spiritual meaning remain prominent. By foregrounding community voices, the study contributes to critical debates on authenticity and heritage in tourism, emphasizing that cultural sustainability in Bali requires more than preservation policies; it demands local participation in defining what authenticity means in practice.